CAMPUR KODE DAN FAKTOR PENYEBAB CAMPUR KODE DALAM KANAL YOUTUBE KOREA ROEMIT - Soleha, Dwi Yulianti; Ginanjar, Agi Ahmad (Universitas Batanghari, 2023)
This study aims to examine the mixed codes and causes of code mixes found on Jang Hansol's Korean Roemit Youtube channel. The research uses a qualitative approach with a descriptive method. Data collection is carried out using the free listening technique and the note-taking technique. The results showed that 25 data mixed codes were found, 9 data mixed codes outwards, and 1 mixed codemixed data, the factors causing speakers to mix codes were speakers and speech partners communicating in informal (relaxed) situations, the absence of the right language for the language being used, and the relationship of a language to the topic being talked about. As a suggestion, further research can be developed again in the types and factors causing the occurrence of mixed codes so that more in-depth research needs to be carried out.